Nuclear levels and patterns of histone H3 modification and HP1 proteins after inhibition of histone deacetylases - Bártová, Eva; Pacherník, Jirí; Harnicarová, Andrea; Kovarík, Ales; Kovaríková, Martina; Hofmanová, Jirina; Skalníková, Magdalena; Kozubek, Michal; Kozubek, Stanislav (Journal of cell science, 2005)
The effects of the histone deacetylase inhibitors (HDACi) trichostatin A (TSA) and sodium butyrate (NaBt) were studied in A549, HT29 and FHC human cell lines. Global histone hyperacetylation, leading to decondensation of interphase chromatin, was characterized by an increase in H3(K9) and H3(K4) dimethylation and H3(K9) acetylation. The levels of all isoforms of heterochromatin protein, HP1, were reduced after HDAC inhibition. The observed changes in the protein levels were accompanied by changes in their interphase patterns. In control cells, H3(K9) acetylation and H3(K4) dimethylation were substantially reduced to a thin layer at the nuclear periphery, whereas TSA and NaBt caused the peripheral regions to become intensely acetylated at H3(K9) and dimethylated at H3(K4). The dispersed pattern of H3(K9) dimethylation was stable even at the nuclear periphery of HDACi-treated cells. After TSA and NaBt treatment, the HP1 proteins were repositioned more internally in the nucleus, being closely associated with interchromatin compartments, while centromeric heterochromatin was relocated closer to the nuclear periphery. These findings strongly suggest dissociation of HP1 proteins from peripherally located centromeres in a hyperacetylated and H3(K4) dimethylated environment. We conclude that inhibition of histone deacetylases caused dynamic reorganization of chromatin in parallel with changes in its epigenetic modifications.
Keywords: histony; buňky HT-29; Chromosomal Proteins, Non-Histone; homolog proteinu s chromoboxem 5; Cell Line; nádory plic; Cell Nucleus; Cell Line, Tumor; Lung Neoplasms; histondeacetylasy; Histone Deacetylase Inhibitors; malobuněčný karcinom; Histone Deacetylases; Fetus; buněčné jádro; Enzyme Inhibitors; Hydroxamic Acids; Interphase; chromatin; kyselina máselná; interfáze; Chromatin; plod; lidé; inhibitory histondeacetylas; Humans; kyseliny hydroxamové; Cell Cycle; Colonic Neoplasms; HT29 Cells; Chromobox Protein Homolog 5; buněčné linie; apoptóza; chromozomální proteiny, nehistonové; nádory tračníku; Histones; buněčný cyklus; Butyric Acid; nádorové buněčné linie; inhibitory enzymů; Apoptosis; Carcinoma, Small Cell